Guidance for paediatric emergency departments/rooms and departments of paediatrics on the management of a child suspected of or diagnosed with COVID-19 - Jackowska, Teresa; Marczyńska, Magda; Peregud-Pogorzelski, Jarosław (Pediatria Polska - Polish Journal of Paediatrics, 2020)
The presented guidance describes the basic principles of the management of children admitted to the emergency department (ED), emergency room (ER), or hospital diagnosed or not with COVID-19. This guidance is based on the literature review conducted and is valid at the date of issue. It may evolve over time as our knowledge about the infection increases. The majority of children will develop mild symptoms from the infection. In addition, the majority of children will not have any breathing problems. Current experience suggests that the department of paediatrics will not be involved in the frontline fight against coronavirus. However, we will play a crucial role in that fight, and so we should remember and plan our actions well.